Usability and Quality Evaluation of the "E- Midwife" Mobile Application for Nurse- Midwives in Obstetric Complications: A Randomized Controlled Trial - Santhoshkumari Mohan; Hepsibah S Sharmil (Shiraz University of Medical Sciences, 2023)
Background: Obstetric complications are illnesses that develop during childbirth. Smartphones,which facilitate the use of prompt features in the early diagnosis of challenges and quick delivery ofrespectful maternity care, are one of the most recent advances in health technology. The key objectiveof this project is to evaluate the usability and quality of the "E-Midwife" mobile application for nursemidwives,which focuses on obstetric complications.Methods: This study is a component of a randomized controlled trial on nurse-midwives. This projectfollowed a four-step approach: content development phase, app design phase, app development phase,and usability testing phase. The app was developed using extensive flowcharts, a definition of thenavigational framework, a structured database, and user-friendly software. 140 out of the 196 nursemidwiveswere allocated to the intervention (n=70) and control group (n=70), using random allocation.The intervention group used the application for 8 weeks. Usability and quality of the application wereassessed using the system usability scale and the mobile application rating scale, respectively. SPSSstatistical software, version 17, was used to analyze the dataResults: The overall score of the usability testing of E-Midwife was 82.75±0.68 The total mean scoreof quality was 3.77±0.86. Therefore, it was shown to have good usability and quality.Conclusion: The E-midwife mobile application has a high usability and quality which makes its usageeffective and efficient. It is recommended that these similar mobile apps should be used along withother educational methods for educating the nurse-midwives.Trial Registration Number: CTRI/2022/03/040857.